Principles of Turbomachinery (2nd Edition) - Korpela, Seppo A. (John Wiley & Sons, 2019)
In mechanical engineering, turbomachinery describes machines that transfer energy between a rotor and a fluid, including turbines, compressors, and pumps. Aiming for a unified treatment of the subject matter, with consistent notation and concepts, this new edition of a highly popular book provides all new information on turbomachinery, and includes 50% more exercises than the previous edition. It allows readers to easily move from a study of the most successful textbooks on thermodynamics and fluid dynamics to the subject of turbomachinery. The book also builds concepts systematically as progress is made through each chapter so that the user can progress at their own pace. This book provides comprehensive coverage of everything readers need to know, including chapters on: thermodynamics, compressible flow, and principles of turbomachinery analysis. The book also looks at steam turbines, axial turbines, axial compressors, centrifugal compressors and pumps, radial inflow turbines, hydraulic turbines, hydraulic transmission of power, and wind turbines. New chapters on droplet laden flows of steam and oblique shocks help make this an incredibly current and well-rounded resource for students and practicing engineers.